Hipertexto, hipermédia e media do conhecimento: representação distribuída e aprendizagens flexíveis e colaborativas na Web - Paulo Dias (Universidade do Minho, 2000)
This article presents an analysis of the hypertext and hypermedia educational approach in the development of learning environments. The interactive processes of the knowledge media, the hypertext flexibility, the distributed representations and the collaborative learning establish reference dimensions to the conception and organisation of the learning communities in the Web.